Preparation method and application of epoxy acrylate composite viscosity reducer

Synthesize epoxy acrylate composite viscosity reducing agent by emulsion polymerization, and introduce hydrogen bonds and hydrophobic groups by GMA, solving the problem of unstable thick oil emulsion in the prior art, and achieving improvement in fluidity and viscosity of heavy oil Reduced, with good thermal stability and viscosity reduction effect.

CN119264324APending Publication Date: 2025-01-07NINGBO INST OF DALIAN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411623244.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The synthesis process of existing amphiphilic polymer viscosity reducing agents is complicated, and acrylamide is unstable in water, resulting in unstable thick oil emulsion and it is difficult to effectively reduce the viscosity of heavy oil.

Method used

The epoxy acrylate composite viscosity reducing agent was synthesized by emulsion polymerization. By adding glycidyl methacrylate (GMA) monomer, hydrogen bonds and hydrophobic groups were formed, and the thermal stability and interface activity of the polymer were improved to form stability. oil and water lotion.

Benefits of technology

The fluidity of heavy oil is improved and the viscosity is significantly reduced. The polymer is evenly dispersed in water, with good thermal stability and viscosity reduction effect, simplifying the synthesis process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119264324A_ABST
    Figure CN119264324A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of amphiphilic polymer viscosity reducers, and particularly relates to a preparation method and application of an acrylate composite viscosity reducer. The preparation method comprises the following steps: preparing a pre-emulsion: firstly, magnetically stirring an emulsifier and deionized water at room temperature; sequentially adding butyl acrylate, ethyl methacrylate, acrylic acid, N-hydroxymethyl acrylamide, glycidyl methacrylate, an initiator and a reducing agent to prepare a pre-emulsion; (2) synthesizing a seed emulsion: stirring and heating the obtained partial pre-emulsion, adding a reducing agent aqueous solution for the first time, then adding an initiator aqueous solution, adding the reducing agent aqueous solution for the second time, adjusting the temperature, and adding the reducing agent aqueous solution for the third time; and (3) when the seed emulsion shows a blue phase, adding the rest pre-emulsion and the initiator aqueous solution at the same time to obtain a target product. The method has the advantages of high synthesis efficiency, good thermal stability of the target product, uniform dispersion in water, improvement of the fluidity of the thickened oil, and effective reduction of the viscosity of the thickened oil.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of amphiphilic polymer viscosity reducers, and in particular relates to a preparation method and application of an epoxy acrylate composite viscosity reducer. Background Art

[0002] With the continuous growth of energy demand and the continuous consumption of dilute oil resources, the development and utilization of heavy oil has received widespread attention. A common method to reduce the viscosity of heavy oil is to form an oil-in-water emulsion, which has been widely studied. The traditional method of adding surfactants to form emulsions is effective, but surfactants are expensive and easily adsorbed by rock formations. The alkali-surfactant-polymer system is complex and can be separated by chromatography, which reduces the recovery rate of heavy oil. In recent years, the research on amphiphilic polymers has received increasing attention. Some scholars have confirmed that amphiphilic polymers are conducive to the emulsification of heavy oil. Higher hydrophobic groups can improve the ability to reduce surface tension, while hydrogen bonds and long-chain groups will destroy the asphaltene structure in heavy oil.

[0003] Prior art has developed water-soluble amphiphilic polymers with strong hydrogen bonds, polar functional groups and acrylamide. The addition of hydrogen-bonding polar groups increases the content of surfactant monomers in the polymer, while the addition of water-soluble hydrophobic long chains increases the surface and interfacial activity of the terpolymer. This improves the emulsification and viscosity reduction capabilities. One solution is to synthesize an amphiphilic polymer by free radical polymerization, which can reduce the interfacial tension between oil and water to ultra-low levels. This reduces the shrinkage of droplets at the interface, promotes oil-water mixing and emulsification, and converts high-viscosity heavy oil into low-viscosity oil-in-water (O / W) emulsions, thereby improving the flow of heavy oil. Another solution is to synthesize an amphiphilic terpolymer by free radical copolymerization. These copolymers have the potential to destroy the asphaltene structure through the formation of hydrogen bonds, interact with heavy oil through hydrophobic groups, and dissociate the resin due to strong polar groups. However, due to the low surface activity, the formed water-in-water emulsion is prone to rapid self-decomposition and instability, resulting in complete separation of oil and water. At present, most of the research on amphiphilic polymer viscosity reducers focuses on the preparation of polymers containing acrylamide units by free radical polymerization. The synthesis process is relatively complicated, and it is usually necessary to consider the dehydration, purification and solubility of the polymer after synthesis. More importantly, acrylamide is easily hydrolyzed in water and lacks stability at high temperatures. Therefore, there is an urgent need for a viscosity reducer with simple synthesis and stable performance. Summary of the invention

[0004] The present invention aims to overcome the deficiencies of the prior art and provide a method for preparing an epoxy acrylate composite viscosity reducer which has high synthesis efficiency, good thermal stability of the target product, is evenly dispersed in water, can improve the fluidity of heavy oil, and effectively reduce the viscosity of heavy oil.

[0005] The present invention also provides an application of a product obtained by the preparation method of the epoxy acrylate composite viscosity reducer in reducing the viscosity of heavy oil.

[0006] To solve the above technical problems, the present invention is achieved as follows:

[0007] The preparation method of the acrylate composite viscosity reducer comprises the following steps in sequence:

[0008] (1) Preparation of pre-emulsion: First, the emulsifier and deionized water are magnetically stirred at room temperature, and then butyl acrylate (BA), ethyl methacrylate (MMA), acrylic acid (AA), and N-hydroxymethyl acrylamide (N-MAM) are added respectively to prepare a pre-emulsion;

[0009] (2) Synthesis of seed emulsion: stirring and heating the pre-emulsion obtained in step (1), then adding a buffer solution, then adding an initiator solution, adding a reducing agent solution for the first time, adjusting the temperature, and adding a reducing agent solution for the second time to obtain a seed emulsion;

[0010] (3) Synthesis of target product: When the seed emulsion in step (2) shows a blue phase, the remaining pre-emulsion and the initiator aqueous solution obtained in step (1) are added to obtain the target product, the acrylate composite viscosity reducer.

[0011] Furthermore, the buffer is sodium bicarbonate; the initiator is ammonium persulfate; and the reducing agent is sodium bisulfite.

[0012] Furthermore, the weight percentages of the emulsifier, deionized water, butyl acrylate, ethyl methacrylate, acrylic acid, N-hydroxymethyl acrylamide, sodium bicarbonate, ammonium persulfate and sodium bisulfite are 1.8%, 67.39%, 13.5%, 15%, 0.6%, 0.9%, 0.02%, 0.6% and 0.19%, respectively.

[0013] Furthermore, in step (1), the emulsifier includes sodium lauryl sulfate and polyoxyethylene octylphenol ether-10; wherein the mass ratio of sodium lauryl sulfate to polyoxyethylene octylphenol ether-10 is 4:5.

[0014] Furthermore, in the step (2), the pre-emulsion obtained in the step (1) with a volume content of 1 / 4 is stirred and heated, then, a sodium bicarbonate aqueous solution is added at 50° C., and then an ammonium persulfate aqueous solution is added at 60° C., and then a sodium bisulfite aqueous solution is added for the first time, the temperature is adjusted, and a sodium bisulfite aqueous solution is added for the second time to obtain a seed emulsion.

[0015] Furthermore, in the step (3), when the seed emulsion of step (2) shows a blue phase, 3 / 4 of the volume content of the pre-emulsion obtained in step (1) and the initiator aqueous solution are added simultaneously at 80° C., and the mixture is kept warm at 80° C. for 2 hours, and the pH value is adjusted to be neutral or weakly alkaline, thereby obtaining the target product, the acrylate composite viscosity reducer.

[0016] Furthermore, glycidyl methacrylate (GMA) is added in step (1).

[0017] Furthermore, the weight percentage of glycidyl methacrylate (GMA) in the acrylic monomer is 0-15%.

[0018] As a preferred embodiment, the weight percentages of the emulsifier, deionized water, butyl acrylate, ethyl methacrylate, acrylic acid, N-hydroxymethyl acrylamide, sodium bicarbonate, ammonium persulfate and sodium bisulfite are 1.72%, 64.48%, 12.9%, 14.4%, 0.57%, 0.86%, 0.02%, 0.57% and 0.18%, respectively, and the rest is glycidyl methacrylate (GMA).

[0019] The product obtained by the preparation method of the above-mentioned acrylic ester composite viscosity reducer is used in reducing the viscosity of heavy oil, which comprises heating the heavy oil and performing a thinning treatment to obtain a reference oil sample; then mixing and stirring m-xylene with a surfactant and the acrylic ester composite viscosity reducer to obtain a heavy oil emulsion; the mass ratio of the acrylic ester composite viscosity reducer to the heavy oil is 2 to 8%.

[0020] With the assistance of the redox initiation system, the acrylic monomer undergoes free radical polymerization through the carbon-carbon double bond C=C to generate a polyacrylate chain with both hydrogen bonds and hydrophobic groups. With the addition of the epoxy monomer GMA, the carbon-carbon double bond C=C of GMA participates in free radical copolymerization, introducing the epoxy group segment into the main chain of the polyacrylate to form a copolymer containing epoxy in the side chain. During the polymerization process, some epoxy compounds in GMA may undergo an epoxy ring-opening reaction with the hydroxyl group to form an ether bond.

[0021] The specific synthetic route is as follows:

[0022]

[0023] The present invention uses butyl acrylate (BA), ethyl methacrylate (MMA), acrylic acid (AA) and hydroxymethyl acrylamide (N-MAM) as monomers, adopts emulsion polymerization to prepare a viscosity reducer, and synthesizes a series of acrylate composite viscosity reducers by adding different contents of glycidyl methacrylate (GMA) monomers. Due to its amphiphilicity, the acrylate composite viscosity reducer polymer can be adsorbed on the oil-water interface of heavy oil to improve the strength of the oil-water interface film. The introduction of GMA can bring more hydrogen bonds and hydrophobic groups to the polymer, and some epoxy groups may react with hydroxyl groups to form a more tightly cross-linked structure of the polymer, thereby improving the strength of the oil-water interface film. The present invention uses Fourier transform infrared spectroscopy (FTIR) to analyze the reaction mechanism of the epoxy acrylate composite viscosity reducer. In addition, the stability of the polymer and the difference of the epoxy acrylate composite viscosity reducer after adding the GMA monomer are analyzed by particle size and Zeta potential. Thermogravimetric (TG) analysis shows that GMA modification significantly improves the thermal stability of the epoxy acrylate composite viscosity reducer. The viscosity reduction test results show that the viscosity of the heavy oil is significantly reduced and the viscosity reduction rate is significantly improved. The present invention successfully develops a novel epoxy acrylate composite viscosity reducer through a simple synthesis method, which is evenly dispersed in water and can be directly added in the form of an emulsion. Through the synergistic effect between emulsion polymerization and acrylate monomers, the fluidity of the heavy oil can be improved and the viscosity of the heavy oil can be effectively reduced. The hydrogen bonds of the polymer can destroy the internal structure of the heavy oil, and the hydrophobic groups and network structure of the polymer can form a stable emulsion with the heavy oil. The synthesis method of the present invention is simple, stable, and efficient, and has good cost-effectiveness and a significant viscosity reduction effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The infrared spectra of viscosity reducers with different GMA contents;

[0025] Figure 2 is the particle size distribution curve of viscosity reducer with different GMA contents;

[0026] Figure 3 TG curves of viscosity reducers with different GMA contents;

[0027] Figure 4 The viscosity changes of W15 epoxy acrylate composite viscosity reducer of different concentrations at different shear rates of the present invention;

[0028] Figure 5 The graph shows the viscosity reducing effect of heavy oil with different W15 viscosity reducer contents in the present invention. DETAILED DESCRIPTION

[0029] In order to make those skilled in the art better understand the technical solution of the present invention, the present invention is further described below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. These embodiments should be understood to be only used to illustrate the present invention and not to limit the scope of protection of the present invention. After reading the contents recorded in the present invention, all other embodiments obtained after various changes or modifications made to the present invention based on the technical solution and embodiments of the present invention also fall within the scope of protection of the claims of the present invention. The experimental methods in the following embodiments are conventional methods unless otherwise specified.

[0030] Ethyl methacrylate (MMA, AR), butyl acrylate (BA, AR), acrylic acid (AA, AR), N-hydroxymethyl acrylamide (N-MAM, AR), glyceryl methacrylate (GMA, AR), ammonium persulfate (APS, AR), sodium bisulfite (SBS, AR) were purchased from Anhui Zesheng Technology Co., Ltd., polyoxyethylene octylphenol ether-10 (OP-10, AR) was purchased from Beijing Inokai Technology Co., Ltd., sodium dodecyl sulfate (SDS, AR) was purchased from Shanghai Bid Pharmaceutical Technology Co., Ltd., and sodium bicarbonate (NaHCO3, AR) was purchased from Tianjin Beichen Fangzheng Reagent Factory. Meta-xylene (AR) and disodium lauryl polyoxyethylene ether sulfosuccinate (MES, AR) were purchased from Shanghai McLean Biochemical Technology Co., Ltd. All chemical reagents can be directly used in the experiment without any purification.

[0031] Example:

[0032] 1. Basic raw materials of W0 viscosity reducer

[0033] Butyl acrylate (BA, AR) and ethyl methacrylate (MMA, AR) are selected to improve the solubility of the polymer in heavy oil through polar groups, among which ethyl and butyl provide more hydrophobic groups. N-hydroxymethyl acrylamide (N-MAM, AR) is selected to provide strong hydrogen bonds; acrylic acid (AA, AR) is selected to provide hydrogen bonds for the polymer.

[0034] In a 500 mL four-necked round-bottom flask equipped with a mechanical stirrer, a thermocouple temperature tester, a reflux condenser and a constant pressure separation funnel, an acrylic ester viscosity reducer was prepared by a semi-continuous emulsion polymerization method. The basic components for preparing the acrylic ester viscosity reducer are shown in Table 1.

[0035] Table 1

[0036]

[0037]

[0038] 2. Preparation of W0 viscosity reducer

[0039] First, add the emulsifier (SDS:OP-10 mass ratio of 4:5) and deionized water into a 500ml round-bottom flask and stir magnetically at room temperature for 10 minutes. Then, add all the acrylic monomers in Table 1 [butyl acrylate (BA), ethyl methacrylate (MMA), acrylic acid (AA), N-hydroxymethyl acrylamide (N-MAM)] into the round-bottom flask respectively, and continue stirring for 30 minutes to prepare a pre-emulsion. Next, add 1 / 4 of the volume content of the above pre-emulsion into an empty 500ml four-necked flask, stir mechanically, and let the temperature rise. Then, add sodium bicarbonate (NaHCO3, AR) aqueous solution (mass concentration of 0.02wt%) to the above four-necked flask at 50°C, add an initiator aqueous solution (APS with a mass concentration of 2.34wt%) at 60°C, and add a reducing agent aqueous solution (SBS with a mass concentration of 3.66wt%) after 30 seconds. Adjust the temperature to the desired temperature, and add SBS aqueous solution (mass concentration of 0.9wt%) to synthesize seed emulsion after 30 seconds. Once the seed emulsion shows a blue phase, drip the remaining pre-emulsified emulsion and initiator aqueous solution (mass concentration of 3.1wt%) at 80°C. Complete the dripping after 2 hours and keep warm at 80°C for 2 hours. The weight percentages of the emulsifier (SDS, OP-10), deionized water, butyl acrylate (BA), ethyl methacrylate (MMA), N-hydroxymethyl acrylamide (N-MAM), sodium bicarbonate (NaHCO3), ammonium persulfate (APS), sodium bisulfite (SBS) and acrylic acid (AA) are: 1.8%, 67.39%, 13.5%, 15%, 0.9%, 0.02%, 0.6%, 0.19%, 0.6%, respectively. Finally, the prepared emulsion was cooled to room temperature, the pH value was adjusted to neutral or weakly alkaline with ammonia water, filtered with a 200-mesh sieve, and the collected emulsion was named W0 viscosity reducer.

[0040] 3. Preparation of W15 epoxy acrylate composite viscosity reducer

[0041] The preparation method of epoxy acrylate composite viscosity reducer is similar to that of acrylate viscosity reducer (W0 viscosity reducer). Glycidyl methacrylate GMA is introduced into the system at the pre-emulsification stage. The addition amount of glycidyl methacrylate GMA is fixed at 0, 5%, 10%, and 15% according to the mass percentage of acrylic monomers. These samples are named Wm (m = 0, 5, 10, 15), representing epoxy acrylate composite viscosity reducer prepared with mwt% GMA.

[0042] First, add the emulsifier (SDS:OP-10 mass ratio of 4:5) and deionized water into a 500ml round-bottom flask and stir magnetically at room temperature for 10 minutes. Then, add all the acrylic monomers [butyl acrylate (BA), ethyl methacrylate (MMA), acrylic acid (AA), N-hydroxymethyl acrylamide (N-MAM)] and glycidyl methacrylate (GMA) in Table 1 into the round-bottom flask respectively, and continue stirring for 30 minutes to prepare a pre-emulsion. Next, add 1 / 4 of the above pre-emulsion by volume into an empty 500ml four-necked flask, stir mechanically, and let the temperature rise. Then, add sodium bicarbonate (NaHCO3, AR) aqueous solution (mass concentration of 0.02wt%) into the above four-necked flask at 50°C, add an initiator aqueous solution (APS with a mass concentration of 2.34wt%) at 60°C, and add a reducing agent aqueous solution (SBS with a mass concentration of 3.66wt%) after 30 seconds. Adjust the temperature to the desired temperature, and add SBS aqueous solution (mass concentration of 0.9wt%) to synthesize seed emulsion after 30 seconds. Once the seed emulsion shows a blue phase, drip the remaining pre-emulsified emulsion and initiator aqueous solution (mass concentration of 3.1wt%) at 80°C. Complete the dripping after 2 hours and keep warm at 80°C for 2 hours. The weight percentages of the emulsifier, deionized water, butyl acrylate, ethyl methacrylate, acrylic acid, N-hydroxymethyl acrylamide, sodium bicarbonate, ammonium persulfate and sodium bisulfite are: 1.72%, 64.48%, 12.9%, 14.4%, 0.57%, 0.86%, 0.02%, 0.57% and 0.18% respectively, and the rest is glycidyl methacrylate (GMA), that is, the weight percentage of glycidyl methacrylate (GMA) in the acrylic monomer (in Table 1) is 15%. Finally, the prepared emulsion was cooled to room temperature, the pH value was adjusted to neutral or weakly alkaline with ammonia water, filtered with a 200-mesh sieve, and the collected emulsion was named W15 epoxy acrylate composite viscosity reducer.

[0043] 4. Application of epoxy acrylate composite viscosity reducer W15

[0044] First, the heavy oil (Zhenhai Refining and Chemical PFO) was heated at 150°C for 20 minutes, and 20% thin oil (Zhenhai Refining and Chemical PGO) was added for thinning treatment, and stirred with a stirring rod for 2 minutes to obtain a reference oil sample, represented by A0 (where PFO and PGO are both from Ningbo Zhenhai Refining and Chemical Co., Ltd.). On this basis, sample A0 was allowed to stand until the temperature dropped to 80°C. Meta-xylene with a mass concentration of 4% was mixed with a disodium lauryl alcohol polyoxyethylene ether sulfosuccinate aqueous solution (mass concentration of 0.8wt%) and an epoxy acrylate composite viscosity reducer W15, and stirred with a stirring rod for 2 minutes. The mass ratio of meta-xylene and disodium lauryl alcohol polyoxyethylene ether sulfosuccinate aqueous solution to heavy oil was fixed, and the mass of the epoxy acrylate composite viscosity reducer accounted for 2%, 4%, 6% and 8% of the mass of the heavy oil, respectively. Add the mixture. Finally, the mixture was stirred with a stirring rod to immediately form a heavy oil emulsion. The obtained samples were denoted as A1 (2 wt %), A2 (4 wt %), A3 (6 wt %) and A4 (8 wt %), respectively.

[0045] 5. Polymer Characterization

[0046] The chemical structure of the synthesized latex was analyzed by FT-IR (Nicoleti S50, Thermo Fisher Scientific Co., USA).

[0047] The particle size, particle size distribution and Zeta potential of the emulsion were measured using a nano laser particle size analyzer (Malvern, Nano ZS90). A drop of the emulsion was diluted with 20 ml of deionized water, ultrasonicated for 15 minutes, and each sample was scanned 3 times.

[0048] 6. Thermal performance analysis

[0049] The thermal stability of the viscosity reducer was tested by a thermogravimetric analyzer (TGA, Mettler Toledo Co. Swiss Confederation) in the temperature range of 20 to 800 °C, a heating rate of 10 °C / min, and a N2 flow rate of 30 ml / min.

[0050] 7. Evaluation of viscosity reduction effect

[0051] The viscosity of the dispersion medium in the emulsion was determined using an Anton Paar MCR 301 rheometer with a concentric cylinder system (cup radius 14.466 mm, rotor radius 13.330 mm) in a shear rate range of 0.01 s -1 ~100s -1 The test temperature is 50℃.

[0052] The viscosity reduction ratio (VRR) is used to evaluate the viscosity reduction ability of polymers on heavy oil:

[0053] VRR(%)=(η0–η1)×100 / η0

[0054] Among them, η0 is the reference viscosity of heavy oil before viscosity reduction, which is 1596 mPa·s; η1 is the corresponding viscosity of water-in-oil emulsion after viscosity reduction.

[0055] In order to verify the successful introduction of GMA into pure acrylic viscosity reducer. Figure 1 , Figure 1 Infrared spectra of GMA (W0), 5wt% GMA (W5), 10wt% GMA (W10) and 15wt% GMA (W15).

[0056] In the FTIR spectrum of pure acrylic viscosity reducer W0, -CH3 and -CH2- are at 2956 cm -1 and 2870cm -1 There are stretching vibration absorption peaks at 3440 cm-1, and -NH and -OH at 3440 cm-1. -1 There is a stretching vibration absorption peak at 1727cm -1 In the FTIR graph of GMA (W5, W10, W15), 909cm -1 is the tensile vibration of epoxy resin, 1096cm -1 The absorption peak at is the COC stretching vibration, which may be due to the ring opening of some epoxy groups, indicating that GMA has been successfully introduced into the polyacrylate molecular chain.

[0057] 8. Effect of GMA dosage on viscosity reducer stability

[0058] The particle size distribution curves of the epoxy acrylate composite viscosity reducer when the GMA content is 0wt%, 5wt%, 10wt% and 15wt% are as follows: Figure 2As shown. The particle size distribution of the synthesized epoxy acrylate composite viscosity reducer is relatively uniform, unimodal, and normally distributed, as shown in the figure. The polymer dispersion index (PdI) is used to characterize the molecular weight distribution of the polymer. The higher the PdI, the wider the molecular weight distribution, and the lower the PdI, the more uniform the molecular weight distribution. When the GMA content is 0wt% to 10wt% (50 to 400nm, PDI0.066 to 0.119), the particle size distribution is narrow; when the GMA content is 15wt% (50 to 700nm, PDI 0.173), the particle size distribution is wide. This is consistent with the particle size dispersion index in Table 2. It can be seen from Table 2 that when the GMA content increases from 0wt% to 10wt%, the emulsion particle size of the epoxy acrylate composite viscosity reducer synthesized by GMA does not change much; when the GMA content is 15wt%, the particle size of the emulsion increases. This is due to the large amount of GMA, which introduces more acrylate chains and epoxy groups, thereby strengthening the structure of the polymer. Therefore, the particle size of the emulsion gradually increases. The zeta potential of the synthesized epoxy acrylate composite viscosity reducer is in the range of ±40 to ±60 mV, indicating that the viscosity reducer has good stability and is not easy to coagulate.

[0059] Table 2

[0060]

[0061] See also Figure 3 As shown, Figure 3 Particle size distribution curves of epoxy acrylate composite viscosity reducer when the GMA content is 0wt% (W0), 5wt% (W5), 10wt% (W10) and 15wt% (W15).

[0062] 9. Thermal stability measurement

[0063] The thermal properties of W0-W15 were tested by thermogravimetric analyzer. Figure 3 The thermal degradation behavior of W0-W15 under nitrogen at 20℃~800℃ is shown in Figure 3As shown. TG curves of epoxy acrylate polymers with GMA contents of 0wt% (W0), 5wt% (W5), 10wt% (W10) and 15wt% (W15). All samples showed similar degradation behavior. The weight loss at 100-200°C was due to the removal of unremoved water molecules, while the weight loss at 350-480°C was due to the decomposition of macromolecular chains. The initial decomposition temperatures were 366°C, 368°C, 368°C and 370°C, respectively, and the final decomposition temperatures were 450°C, 475°C, 493°C and 517°C, respectively. With the increase of GMA content, the thermal decomposition temperature and thermal stability of the polymer increased within a certain range. Compared with W15, the final thermal degradation temperature of W0 increased from 450°C to 517°C. This may be due to the introduction of epoxy groups by the addition of GMA, which requires more heat to decompose, some of which can react with -OH, enhancing the spatial network structure of the polymer and further improving the thermal stability. The results show that with the increase of GMA content, the thermal stability is improved. Among them, W15 has the best thermal stability, which is better than the other three polymers. In addition, with the addition of GMA, the thermal degradation of the resin is delayed, which can be seen from Figure 3 This is confirmed by the insertion curve of . Within a certain range, the degree of delayed thermal degradation increases with the increase of GMA content. After adding 15wt% GMA, the maximum weight loss temperature increases by about 12°C. Therefore, the W15 copolymer with the most GMA introduced exhibits the highest thermal stability and is more suitable for viscosity reduction of heavy oil.

[0064] 10. Heavy oil viscosity reduction performance of polymers

[0065] The selected W15 epoxy acrylate composite viscosity reducer is more suitable for heavy oil viscosity reduction. It forms an O / W emulsion by wrapping the heavy oil in a polymer aqueous solution, which improves the fluidity of the heavy oil and reduces the viscosity of the heavy oil. In addition, W15 can be mixed with organic solvents to produce a synergistic effect. Xylene essentially changes the composition and properties of heavy oil. It redistributes heavy oil molecules through its own special structure, decomposes the macromolecular structure, and destroys the strong adhesion of heavy oil. Adding m-xylene to the epoxy acrylate composite viscosity reducer to assist the viscosity reducer can more effectively improve the viscosity reduction effect. Since the epoxy acrylate composite viscosity reducer is dispersed in the water system and is immiscible with m-xylene, a small amount of surfactant aqueous solution is added, and the two are stirred for heavy oil viscosity reduction.

[0066] Figure 4The viscosity changes of different concentrations of W15 epoxy acrylate composite viscosity reducers at different shear rates and a test temperature of 50°C are shown. As can be seen from the figure, the viscosity of A0-A4 decreases rapidly with the increase of shear rate. According to the literature, the viscosity of heavy oil decreases with the increase of shear rate due to the reduction of entanglement and bonding between heavy oil molecules or emulsions. For example, when the shear rate is 70^-1, the viscosity of A0 is 1596.9mPa·s. In addition, it can be seen from the figure that the viscosity of heavy oil is significantly reduced after the addition of viscosity reducers. For example, after the addition of A1 and A2, the viscosity of heavy oil decreases from 1596.9mPa·s to 910.63mPa·s and 774.68mPa·s, respectively. In addition, with the increase of viscosity reducer content, the decrease in viscosity of heavy oil is more obvious. For example, after the addition of A3, the viscosity of heavy oil drops to 197.86mPa·s, and after the addition of A4, the viscosity of heavy oil drops to 177.42mPa·s.

[0067] Figure 5 The viscosity reduction effect of heavy oil with W15 type viscosity reducer content of 2wt% (A1), 4wt% (A2), 6wt% (A3) and 8wt% (A4). A0-A4 at 70s -1 Viscosity reduction rate under shear rate. VRR was calculated by the viscosity reduction formula, and η0 was 1596.9 mPa·s. With the increase of the content of W15 viscosity reducer, the viscosity reduction rate gradually increased, the viscosity reduction rate of A1 reached 43%, and the viscosity reduction rate of A4 reached 89%. When the W15 content is 2-8%, the viscosity reduction rate can reach 43-89%. The results show that epoxy acrylate viscosity reducer has a good viscosity reduction effect. When a small amount of meta-xylene destroys the structure of heavy oil, the hydrophobic groups in W15 are adsorbed at the oil-water interface, and the polar groups in W15 increase the solubility of the polymer in heavy oil. At the same time, the hydroxyl and amide groups in the polymer form strong hydrogen bonds with the asphaltene in the heavy oil, thereby reducing the viscosity of the heavy oil. Combined with Figure 4 and Figure 5 The viscosity and viscosity reduction rate test results show that the synthesized W15 epoxy acrylate composite viscosity reducer has a satisfactory viscosity reduction effect.

[0068] The particle size and Zeta potential structure analysis of the present invention show that the synthesized viscosity reducer has good stability. In addition, thermogravimetric analysis shows that the thermal stability of the GMA modified resin has been significantly improved, among which the thermal stability of W15 is the best among the four viscosity reducers. The heavy oil viscosity test and viscosity reduction rate show that the higher the W15 content, the more obvious the reduction in heavy oil viscosity and the higher the viscosity reduction rate. Specifically, after adding 8% of W15 epoxy acrylate, the viscosity reduction rate of the heavy oil reaches 89%, showing an excellent viscosity reduction effect.

[0069] The above-described embodiments are only preferred embodiments of the present invention and are not intended to limit the present invention. It should be noted that for those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing an acrylic ester composite viscosity reducer, characterized in that: The steps are as follows: (1) Preparation of pre-emulsion: First, the emulsifier and deionized water are magnetically stirred at room temperature, and then butyl acrylate (BA), ethyl methacrylate (MMA), acrylic acid (AA), and N-hydroxymethyl acrylamide (N-MAM) are added respectively to prepare a pre-emulsion; (2) Synthesis of seed emulsion: stirring and heating the pre-emulsion obtained in step (1), then adding a buffer solution, then adding an initiator solution, adding a reducing agent solution for the first time, adjusting the temperature, and adding a reducing agent solution for the second time to obtain a seed emulsion; (3) Synthesis of target product: When the seed emulsion in step (2) shows a blue phase, the remaining pre-emulsion and the initiator aqueous solution obtained in step (1) are added to obtain the target product, the acrylate composite viscosity reducer.

2. The method for preparing the acrylic ester composite viscosity reducer according to claim 1, characterized in that: The buffer is sodium bicarbonate; the initiator is ammonium persulfate; and the reducing agent is sodium bisulfite.

3. The method for preparing the acrylic ester composite viscosity reducer according to claim 2, characterized in that: The weight percentages of the emulsifier, deionized water, butyl acrylate, ethyl methacrylate, acrylic acid, N-hydroxymethyl acrylamide, sodium bicarbonate, ammonium persulfate and sodium bisulfite are 1.8%, 67.39%, 13.5%, 15%, 0.6%, 0.9%, 0.02%, 0.6% and 0.19% respectively.

4. The method for preparing the acrylic ester composite viscosity reducer according to claim 3, characterized in that: In the step (1), the emulsifier includes sodium lauryl sulfate and polyoxyethylene octylphenol ether-10; wherein the mass ratio of sodium lauryl sulfate to polyoxyethylene octylphenol ether-10 is 4:

5.

5. The method for preparing the acrylic ester composite viscosity reducer according to claim 4, characterized in that: In the step (2), the pre-emulsion obtained in the step (1) with a volume content of 1 / 4 is stirred and heated, then a sodium bicarbonate aqueous solution is added at 50° C., and then an ammonium persulfate aqueous solution is added at 60° C., and then a sodium bisulfite aqueous solution is added for the first time, the temperature is adjusted, and a sodium bisulfite aqueous solution is added for the second time to obtain a seed emulsion.

6. The method for preparing the acrylic ester composite viscosity reducer according to claim 5, characterized in that: In the step (3), when the seed emulsion of step (2) shows a blue phase, 3 / 4 of the volume content of the pre-emulsion obtained in step (1) and the initiator aqueous solution are added simultaneously at 80° C., and the mixture is kept at 80° C. for 2 hours, and the pH value is adjusted to be neutral or weakly alkaline, thereby obtaining the target product, the acrylate composite viscosity reducer.

7. The method for preparing the acrylic ester composite viscosity reducer according to claim 1, characterized in that: In the step (1), glycidyl methacrylate (GMA) is added.

8. The method for preparing the acrylate composite viscosity reducer according to claim 7, characterized in that: The weight percentage of glycidyl methacrylate (GMA) in the acrylic monomer is 0-15%.

9. The method for preparing the acrylic ester composite viscosity reducer according to claim 7, characterized in that: The weight percentages of the emulsifier, deionized water, butyl acrylate, ethyl methacrylate, acrylic acid, N-hydroxymethyl acrylamide, sodium bicarbonate, ammonium persulfate and sodium bisulfite are 1.72%, 64.48%, 12.9%, 14.4%, 0.57%, 0.86%, 0.02%, 0.57% and 0.18% respectively, and the rest is glycidyl methacrylate (GMA).

10. Use of the product obtained by the preparation method of the acrylic ester composite viscosity reducer according to any one of claims 1 to 9 in reducing the viscosity of heavy oil, characterized in that: The heavy oil is heated and thinned to obtain a reference oil sample; then m-xylene is mixed and stirred with a surfactant and an acrylic ester composite viscosity reducer to obtain a heavy oil emulsion; the mass ratio of the acrylic ester composite viscosity reducer to the heavy oil is 2-8%.